2007
DOI: 10.1002/cne.21422
|View full text |Cite
|
Sign up to set email alerts
|

Development of the vomeronasal amygdala in anuran amphibians: Hodological, neurochemical, and gene expression characterization

Abstract: The organization of the amygdaloid complex in amphibians possesses major features shared with amniotes. Basic subdivisions have been identified and tentatively compared with their counterparts in other tetrapods. However, problems appeared when trying to find homologies for the amphibian vomeronasal amygdala, the medial amygdala (MeA), because of its embryological origin and, therefore, its evolutionary significance could not be established. Thus, in the present study the main characteristics of the MeA in anu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 84 publications
8
37
1
Order By: Relevance
“…Rabbit anti-GABA shows positive binding with GABA in a dot blot assay and negative binding with bovine serum albumin (BSA; Sigma data sheet). The GABA antibody has been extensively used in amphibians (Bachy and Retaux, 2006;Moreno and Gonzalez, 2007) and was also used in a recent study in adult Drosophila to describe the morphology of GABAimmunoreactive local interneurons in the AL (Seki et al, 2010), thereby demonstrating specificity for GABAergic interneurons in the antennal lobe of Drosophila, similar to our analysis on the same type of neuron in the same species at the larval stage. Even Larkin et al (2010), also using rabbit anti-GABA, showed a similar pattern of GABA-positive neurons within the larval antennal lobe in comparison with our study.…”
Section: Anti-gabasupporting
confidence: 70%
“…Rabbit anti-GABA shows positive binding with GABA in a dot blot assay and negative binding with bovine serum albumin (BSA; Sigma data sheet). The GABA antibody has been extensively used in amphibians (Bachy and Retaux, 2006;Moreno and Gonzalez, 2007) and was also used in a recent study in adult Drosophila to describe the morphology of GABAimmunoreactive local interneurons in the AL (Seki et al, 2010), thereby demonstrating specificity for GABAergic interneurons in the antennal lobe of Drosophila, similar to our analysis on the same type of neuron in the same species at the larval stage. Even Larkin et al (2010), also using rabbit anti-GABA, showed a similar pattern of GABA-positive neurons within the larval antennal lobe in comparison with our study.…”
Section: Anti-gabasupporting
confidence: 70%
“…All amphibians possess a vomeronasal organ and an accessory olfactory bulb [Reiss and Eisthen, 2008], but the projections of the accessory olfactory bulb have been determined experimentally only in anurans [Northcutt and Royce, 1975;Scalia et al, 1991;Moreno and González, 2007] and salamanders [Laberge and Roth, 2005]. It is now confirmed that lepidosirenid lungfishes also possess an accessory olfactory bulb whose primary, if not sole, target is the ipsilateral medial amygdalar nucleus [González et al, 2010], as is the case for anurans and salamanders ( fig.…”
Section: Phylogenetic Considerationsmentioning
confidence: 52%
“…In the white sturgeon, BDA and biocytin are more effective than DiI in labeling secondary olfactory projections, due to the large number of myelinated fibers in the lateral olfactory tract [Northcutt, 2011b], whereas BDA and DiI appear to be equally effective in labeling the pallial connections in goldfish [Northcutt, 2006]. Although biocytin is generally considered a more effective tracer than HRP, both tracers, as well as BDA, reveal comparable secondary olfactory projections in amphibians [Scalia et al, 1991;Laberge and Roth, 2005;Moreno and González, 2007]. The possible bias resulting from the use of different tracers notwithstanding, the available data indicate that there has been a major reduction in the number of telencephalic areas that receive secondary olfactory projections, particularly in anurans.…”
Section: Phylogenetic Considerationsmentioning
confidence: 99%
“…The pattern of staining obtained with this antibody was similar to that obtained with in situ hybridization for the xGAD67 gene, which encodes an isoform of glutamic acid decarboxylase, an enzyme involved in the synthesis of GABA (compare the results of Brox et al, 2003, andGonzález, 2007a).…”
Section: Controls and Specificity Of The Antibodiesmentioning
confidence: 54%